SISTEM PENDUKUNG KEPUTUSAN PENERIMAAN BEASISWA MENGGUNAKAN FUZZY MULTIPLE ATTRIBUTE DECISION MAKING (FMADM) - Erlan Darmawan; Andri Ramdoni (NUANSA INFORMATIKA, 2012)
SMAN 1 Garawangi is one of state senior high school in Kuningan education department. The education department give some scholarship to distitate students and best student who have good achievement especially in academic aspect. The scholarship is given in order to help the students in finishing heir studies. To help stating the students who will accept the scholarship, it needs a decision supporting system.In decision supporting system process to state the scholarship receivers in SMAN 1 Garawangi, the writer uses fuzzy multiple attribute decision making (FMADM) model and simple additive weighting (SAW) as a method. He chooses this method because it can select best alternative way in deciding the scholarship receivers based on specific criterias. This research is done by selecting score for each attribute, and making the rank process that will state optimal alternative decision about the best student.Based on the analysis, the writer concludes that the system made can help selecting team in stating the candidate to receive scholarship well, proposing scholarship, reducing mistake in selecting candidate and selecting process of scholarship candidate fast.Keywords: Fuzzy Multiple Attribute Decision Making, Simple Additive weighting, Scholarship